2011
DOI: 10.1175/2010mwr3624.1
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Precipitation Forecast Skill as a Function of Ensemble Size and Spatial Scale in a Convection-Allowing Ensemble

Abstract: Probabilistic quantitative precipitation forecasts (PQPFs) from the storm-scale ensemble forecast system run by the Center for Analysis and Prediction of Storms during the spring of 2009 are evaluated using area under the relative operating characteristic curve (ROC area). ROC area, which measures discriminating ability, is examined for ensemble size n from 1 to 17 members and for spatial scales ranging from 4 to 200 km.Expectedly, incremental gains in skill decrease with increasing n. Significance tests compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
98
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 40 publications
4
98
1
Order By: Relevance
“…It is sufficient to be able to estimate accumulations to better than 10% for almost the full length of the simulations. This result is consistent with Clark et al (2011a), which found that convective scale ensembles of nine members had similar skill to the full ensemble of 17 members for the the median ROC curve of probabilistic quantitative precipitation forecasts of 6-hourly accumulations. The standard deviation of the anomalies is remarkably consistent with the error of the mean when estimated using sampling theory (Figure 4), suggesting that the members are indeed independent and identically distributed.…”
Section: Ensemble Sizesupporting
confidence: 91%
“…It is sufficient to be able to estimate accumulations to better than 10% for almost the full length of the simulations. This result is consistent with Clark et al (2011a), which found that convective scale ensembles of nine members had similar skill to the full ensemble of 17 members for the the median ROC curve of probabilistic quantitative precipitation forecasts of 6-hourly accumulations. The standard deviation of the anomalies is remarkably consistent with the error of the mean when estimated using sampling theory (Figure 4), suggesting that the members are indeed independent and identically distributed.…”
Section: Ensemble Sizesupporting
confidence: 91%
“…In order to produce a reliable probabilistic forecast, the individual ensemble member forecasts should be equally likely to occur and cover the range of future states. Following Clark et al (2011), the ideal number of ensemble members is dependent on the point of diminishing returns, i.e., the ensemble size where no new information can be expected by additional members.…”
Section: Introductionmentioning
confidence: 99%
“…To name but a few, there are the COSMO-DE-EPS (Consortium for Small-scale Modeling -EPS, Gebhardt et al, 2011;Peralta et al, 2012;Ben Bouallègue et al, 2013;Kühnlein et al, 2014) at the Deutscher Wetterdienst (DWD), the CP version of UK Met Office's MOGREPS (Met Office Global and Regional Ensemble Prediction System, Bowler et al, 2008;Caron, 2013;Hanley et al, 2013;Tennant, 2015), a storm-scale ensemble forecast (SSEF) run by the Center of Analysis and Prediction of Storms (CAPS) at the University of Oklahoma (Xue et al, 2007Clark et al, 2011;Schumacher et al, 2013;Schumacher and Clark, 2014), WRF-based CP ensemble at NCAR (e.g., Schwartz et al, 2015), and AROME-EPS (e.g., Bouttier et al, 2012) developed at Météo France. A common feature of all of these EPSs is that their horizontal mesh size is equal to or less than 4 km, but mostly between 2 and 3 km.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While progress is continually being made in improving the accuracy of single forecasts -through improvements in the model formulation as well as increases in grid resolution -a complementary approach is the use of ensembles in order to obtain an estimate of the uncertainty in the forecast (Buizza et al, 2005;Montani et al, 2011;Buizza et al, 2007;Bowler et al, 2008;Thirel et al, 2010;Yang et al, 2012;Zhu, 2005;Abhilash et al, 2013;Roy Bhowmik and Durai, 2008;Clark et al, 2011;Tennant and Beare, 2013). Of course, ensemble forecasting systems themselves remain imperfect, and one of the most important problems is insufficient spread in ensemble forecasts, where the forecast tends to cluster too strongly around rainfall values that turn out to be incorrect.…”
Section: Introductionmentioning
confidence: 99%